Business Registration Reforms in Pakistan - Khan, Shamin Ahmad (Washington, DC: World Bank, 2012)
Well structured and implemented policies for registration of business activities constitute an important factor in creating a positive investment climate. This paper describes the reforms in the business registration system in Pakistan during the 1990s. In particular, it describes the creation of the Securities and Exchange Commission of Pakistan (SECP) and subsequent changes in laws and regulations, automation and capacity building, and other facilitation measures. Successful implementation of the reforms was possible due to the financial, administrative and operational autonomy of the SECP and its commitment to upgrade efficiency and quality of services to the public.